Solving social problems by distributed Human Terrain operations - Sapaty, P.S. (Математичні машини і системи, 2015)
The Human Terrain (HT) concept was originally introduced in military for a possible reduction of the loss of lives in international conflicts by appropriate work with local population, like taking into account its peculiarities and needs. In contrast with geographical terrain, HT deals with social, ethnical, cultural, religious, also economic features of human groupings. Considering the HT ideas productive and timely, we are extending their use beyond traditional military areas – for solving diverse social problems, both national and international, using the developed high-level networking ideology and technology. The latter allows large distributed spaces, HT including, to be analysed and impacted by their dynamic coverage with intelligent infrastructures providing global awareness and goal orientation.